Brahma Muhurta and Circadian Rhythms: A Gateway to Optimal Health - Anuradha; Yadav, C R; Pratap Singh, Bhanu; Prabhakaran, Vidhya (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Ayurveda is a holistic science that improves the quality of life and provides curative measures for various disorders, thereby maintaining the health of millions of people. By following the rules of Dinacharya and Ritucharya, one can enhance their longevity. Dinacharya begins with Brahma Muhurta Jagarana. Brahma Muhurta is a specific time that recharges the biological clock in humans and maintains its rhythm and pattern throughout the day. Circadian rhythm is a biological process with an endogenous, entrainable oscillation of approximately 24 h. External factors, such as light and temperature, affect the circadian rhythm in humans. Objectives: To study Brahma Muhurta and circadian rhythm as a gateway to optimal health. Methodology: This research was conducted through a comprehensive review of research articles and classical Ayurveda texts, focusing on Brahma Muhurta and its correlation with the circadian rhythm. Results: A person’s lifestyle also affects this clock, resulting in undesirable traits and diseases. Brahma Muhurta is ideal for meditation and yogic practices, and one’s memory becomes sharp, leading them toward the ultimate goal of yoga, i.e., Moksha. Conclusion: Brahma Muhurta is essential for spiritual evolution, and a person who wakes up early in the morning slows down their aging process. This regimen supports the preservation of health and longevity in individuals free from illness.